پاکستان میں اردو غزل کا مزاج - Dr. Zeenat Bibi; Dr. Muhammad Nasir Afridi; Saeed Ur Rehman (Khayaban - خیابان, 2023)
Ghazal was considered as the pillar of Urdu poetry. This is the biggest reason for its popularity. The expression of ideas in it is the pride of poets. The scope of Ghazal poetry is also more than other genres. Despite the strong opposition to Ghazal in the first three decades of the twentieth century, it has maintained its credibility and quality. Urdu ghazal has gained general acceptance in its internal system due to its elegiac, allegorical, symbolic and technical aesthetics. Apart from ghazal, no other genre of speech has given evidence of contemporary consciousness with intellectual and philosophical diversity. All the themes of partition of India can be covered in Ghazal with passion and feeling. Migrants' pain of being separated from their own, expression of grief, intense emotions, tyranny, political fear and despair, lamentation of an unstable society, social and intellectual problems, linguistic prejudices, psychological confusion, economic degradation, social defeat, new metaphors, symbols, themes and vocabulary, personal feeling of love, physical and technical composition, contemporary issues, figure carving and illustration etc Pakistani ghazal has a unique position in comparison to Indian ghazal. In the period of time, the poets of the first period gave energy to Urdu ghazal in the second period. Thus, in every era, along with the modern generation, ancient and old poets also remained on the poetry tableau with the same dignity and pride. There has been an atmosphere of resistance against Ghazal in every age. Urdu Ghazal continued to move forward with the confluence of modern and ancient and pointing towards the future. Continuity continues its journey. Thus, Urdu ghazal has adopted diverse subjects on a new thematic and intellectual level. But on the technical and technical level, it did not accept the effects of the efforts of thousands of opponents, nor could it be replaced by poetry and independent ghazal. This is a great justification for its development and popularity.